Kombinasi Koagulasi – Flokulasi dan Filtrasi Menggunakan Bahan Alami Pada Limbah Cair Laundry Untuk Menurunkan Parameter TSS dan Kekeruhan - Naufaldy Iqbal Abdillah; Mohamad Mirwan (Jurnal Serambi Engineering, 2024)
The growing population in Indonesia can be used by some people to start a laundry business. Laundry waste has several contents, one of which is Total Suspended Solids (TSS). Coagulation-flocculation is one of the processes that can reduce TSS and turbidity parameters. The coagulation-flocculation process with a stirring speed of 100 rpm and 150 rpm with watermelon seed extract biocoagulant, trembesi seed and commercial aluminium sulphate coagulant for comparison. The next stage of processing is filtration processing using rice husk charcoal, silica sand and gravel. The treatment results are then continued with turbidity measurements and TSS test results. The best treatment results in this coagulation-flocculation combination are turbidity parameters with a percentage removal of 77% watermelon seeds, 70% trembesi seeds and 93% aluminium sulphate. The best test results were obtained for TSS parameters with a percentage removal of 80% watermelon seeds, 69% trembesi seeds and 98% aluminium sulphate. The highest percentage removal in the treatment of washing liquid waste using a combined method of coagulation-flocculation and filtration at a dose of 75 ml/l and a stirring speed of 150 rpm.